Controls on and trends in sediment and particulate organic matter storage by instream wood in north Saint Vrain Creek, Colorado - Pfeiffer, Andrew, author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Baker, Daniel, committee member (Colorado State University. Libraries, 2017)
Sediment and particulate organic matter (POM) retained by wood within the bankfull channel were evaluated for 58 stream reaches at the headwaters of North Saint Vrain Creek, Colorado. Wood-induced storage in headwater regions is hypothesized to be important in buffering downstream transport of material. However, the magnitude of storage has not been thoroughly investigated in relation to different potential control variables (e.g., wood volume, channel gradient, channel confinement, and riparian basal area) and spatial scales (jam, reach, and drainage basin) of control. Multiple and single variable linear regressions informed results. On the jam scale, no relationship was observed between storage and visually estimated jam porosity and permeability. In contrast, the reach-scale volume of stored coarse sediment (gravel, cobble) responds strongly to reach-scale wood volume. Reach-scale fine sediment (sand and finer) volume responds most strongly to wood piece characteristics (average piece length/average channel width and longitudinal spacing) and reach-scale coarse sediment storage. POM storage was most strongly related to riparian controls (channel confinement and riparian forest basal area). These results were translated into a drainage basin-scale analysis in ArcGIS. Despite comprising 14% of the stream network, third-order reaches were found to store 41% of total estimated coarse sediment, 34% of total wood, and 23% of total fine sediment. Large logjams likely exert a high cumulative storage effect in a relatively small portion of the watershed. In contrast, 60% of estimated total POM storage occurs in first-order streams (47% of network stream length). Low transport capacity in these small streams retains highly mobile POM and lateral roots from the nearby riparian forest may serve as retention structures. These results indicate that wood exerts different geomorphic effects depending on its location within the stream network. From a management perspective, road building and campsite development should avoid impacts to first-order streams, as they are important to overall drainage basin POM retention. Third-order streams are hotspots of wood, coarse sediment, and fine sediment; promoting or allowing wood recruitment processes in these areas can facilitate high sediment retention and buffering of downstream transport.